The mechanism of formation of the ultra disperse iron oxide minerals on steel surface in presence of Cu(II), Ag(I), Au(III), Pt (IV), Pd(II) - Lavrynenko, O. (Наноструктурное материаловедение, 2010)
Process of formation of ultra disperse iron oxide minerals on steel surface by its contacts with air oxygen and dispersion medium containing ions of cuprum, argentums, aurum, platinum and palladium was studied. The formation of phase’s hydroxysulphate Green Rust, magnetite and lepidocrocite on steel surface by concentrations of electropositive metals 1–10 mg/dm³ was shown. Mechanism of phase formation occurs by two stages: adsorption of ions from dispersion medium on Green Rust surface with partly reduction of ions and oxidation of GR to magnetite or lepidocrocite and reduction of the rest metal ions on magnetite surface. Interacting iron oxide phases with electropositive ions add colloidal stability to composite particles. Исследован процесс формирования ультрадисперсных железооксидных минералов на поверхности стали при ее контакте с кислородом воздуха и дисперсионной средой, содержащей ионы меди, серебра, золота, платины и палладия. Показано, что при концентрациях электроположительных металлов 1–10 мг/дм³ на поверхности стали образуются структуры гидроксисульфатного Green Rust, магнетита и лепидокрокита. Фазообразование проходит в две стадии: 1) адсорбция ионов дисперсионной среды на поверхности GR с восстановлением части ионов до металла и окислением GR до магнетита или лепидокрокита; 2) восстановление остаточной концентрации ионов электроположительных металлов на поверхности магнетита. Взаимодействие железооксидных фаз с электроположительными ионами придает частицам коллоидную устойчивость. Досліджено процес формування ультрадисперсних залізооксидних мінералів на поверхні сталі при її контакті з киснем повітря та дисперсійним середовищем, яке містить іони міді, срібла, золота, платини та паладію. Показано, що за концентрац ій електропозитивних іонів 1–10 мг/дм³ на поверхні сталі утворюються структури гідроксисульфатного Green Rust, магнетиту й лепідокрокіту. Фазоутворення відбувається у дві стадії: 1) адсорбція іонів дисперсійного середовища на поверхні GR з відновленням частини іонів до металу й окисненням GR до магнетиту або лепідокрокіту; 2) відновлення залишкової концентрації іонів електропозитивних металів на поверхні магнетиту. Взаємодія залізооксидних фаз із електропозитивними іонами надає частинкам колоїдної стійкості.